Distinct myeloid antigen-presenting cells dictate differential fates of tumor-specific CD8+ T cells in pancreatic cancer - Adam L. Burrack; Zoe C. Schmiechen; Michael T. Patterson; Ebony A. Miller; Ellen J. Spartz; Meagan R. Rollins; Jackson F. Raynor; Jason S. Mitchell; Tsuneyasu Kaisho; Brian T. Fife; Ingunn M. Stromnes (JCI Insight, 2022)
We investigate how myeloid subsets differentially shape immunity to pancreatic ductal adenocarcinoma (PDA). We show that tumor antigenicity sculpts myeloid cell composition and functionality. Antigenicity promotes accumulation of type 1 dendritic cells (cDC1), which is driven by Xcr1 signaling, and overcomes macrophage-mediated suppression. The therapeutic activity of adoptive T cell therapy or programmed cell death ligand 1 blockade required cDC1s, which sustained splenic Klrg1+ cytotoxic antitumor T cells and functional intratumoral T cells. KLRG1 and cDC1 genes correlated in human tumors, and PDA patients with high intratumoral KLRG1 survived longer than patients with low intratumoral KLRG1. The immunotherapy CD40 agonist also required host cDC1s for maximal therapeutic benefit. However, CD40 agonist exhibited partial therapeutic benefit in cDC1-deficient hosts and resulted in priming of tumor-specific yet atypical CD8+ T cells with a regulatory phenotype and that failed to participate in tumor control. Monocyte/macrophage depletion using clodronate liposomes abrogated T cell priming yet enhanced the antitumor activity of CD40 agonist in cDC1-deficient hosts via engagement of innate immunity. In sum, our study supports that cDC1s are essential for sustaining effective antitumor T cells and supports differential roles for cDC1s and monocytes/macrophages in instructing T cell fate and immunotherapy response.